Talent in the Professional Practice The Hungarian higher education with a practice based approach, the example of the University of Pécs - Zsuzsanna FARKASNÉ KURUCZ; Balázs LÓRÁND; Gábor BALOGH (Revista de Management Comparat International)
The study presents a research carried out among the students of Hungary’s one of the most successful university faculties, at the University of Pécs Faculty of Business and Economics (PTE KTK). The aim of the study is to highlight the expectations of employers and students regarding professional practice. Our results show that the employers do not focus on creativity. By employing a new staff member fast integration, adaptation, diligent and precise work becomes important. Primarily employers want to hire such appropriate person who fits into their own corporate culture. The PTE KTK students have developed emotional intelligence, which allows for better integration. After presenting the results of empirical research we give a brief overview of the Hungarian and Romanian situation of higher education on the basis of criteria for the European Higher Education Area and the Bologna process. Subsequently, we formulate our recommendations, which are primarily based on the experience of professional practice. The system of professional practice serves as a highly effective feedback, and this shows the removal of the conventional belief. Secondly, there is a demand for bipolar system of knowledge and skill-application (that manifested in competence-principle).